RIBA DAN BANK KONVENSIONAL KAJIAN TEORITIS DENGAN PENDEKATAN TAFSIR - Ahmatnijar Ahmatnijar (Institut agama islam negeri Padangsidimpuan, 2018)
The study of usury if it is associated with a conventional bank remains urgent to do. Besides the Prophet did not explain usury completely because of the close time of his death, this also provided a wider space for Muslims in the field of muamalah which continued to grow. The vocabulary of usury at the time of the Prophet's revelation which was annihilated by the bank's interest now turns out to have experienced a far-reaching development of mahall. However, this condition is a challenge for all Muslims to get collective and comprehensive work in providing alternative solutions in terms of Islamic finance as the best religion and the best people.